3d Metal Complexes Supported by a Bis(imidazolin‐2‐imino)pyridine Pincer Ligand – Synthesis, Structural Characterisation, and Magnetic Properties. Issue 35 (7th November 2014) - Filimon, Sabina‐Alexandra; Petrovic, Dejan; Volbeda, Jeroen; Bannenberg, Thomas; Jones, Peter G.; Freiherr von Richthofen, Carl‐Georg; Glaser, Thorsten; Tamm, Matthias
Abstract: The coordination chemistry of the tridentate pincer ligand TL t Bu, which contains two electron‐rich imidazolin‐2‐imine moieties, has been explored. The reaction of TL t Bu with metal dihalides gave complexes of the general formula [(TL t Bu )MX2 ] (M = Mn, Fe, Co, Ni; X = Cl, Br). These complexes were characterized by X‐ray diffraction analysis, which showed them to have different geometries in the solid state. Although [(TL t Bu )MnCl2 ] (1 ) is best described as distorted square‐pyramidal, the complexes [(TL t Bu )FeCl2 ] (2 ) and [(TL t Bu )CoCl2 ] (3 ) show distorted tetrahedral geometries with the TL t Bu ligand bound in a κ 2 fashion and one of its imidazolin‐2‐imine fragments not coordinated to the metal atom. [(TL t Bu )NiBr]Br (4 ) crystallizes with a slightly distorted square‐planar cation. The reaction of the triflate (OTf) salts [M(OTf)2 · n MeCN] (M = Mn, n = 1; M = Fe, Co, n = 2; OTf = CF3 SO3 ) with TL t Bu resulted in [(TL t Bu )M(OTf)][OTf] (M = Mn, 5 ; M = Fe, 6 ) and [(TL t Bu )Co(NCMe)][OTf]2 (7 ). Complexes6 and7 were characterized by X‐ray diffraction analysis, and both showed distorted square‐planar geometries. Magnetic measurements of5, 6 and7 showed them to possess a S = 5/2, 2 and 1/2 ground states, respectively. The bromide ions in complex4 were exchanged by reaction with AgBF4 to afford [(TL t Bu )Ni(NCMe)][BF4 ]2 (8 ), which showed a distorted square‐planar geometry in the solid state. The reactions of1 and6 with AgOTf resulted in the oxidation of the complexes and the formation of [(TL t Bu )MnCl(OTf)][OTf] (9 ) and [(TL t Bu )Fe(OTf)2 ][OTf] (10 ), respectively. Complexes9 and10 both display distorted square‐pyramidal geometries in the solid state. The ground state of10 was found to be S = 5/2 by superconducting quantum interference device (SQUID) magnetometry measurements. The oxidation of5, 6 and7 with the iodosobenzene derivative ( t BuSO2 )C6 H4 IO was investigated. Although the reactions of6 and7 gave no evidence for the formation of transient oxo species, crystals were obtained from the reaction of5 . These crystals showed the formation of [TL t Bu *Mn(OH)](OTf)2 (11 ), in which one of the t Bu groups of the TL t Bu ligand has undergone a C–H activation by a putative Mn IV =O bond. The complex shows a distorted square‐pyramidal geometry in the solid state, and the carbon atom of the CH‐activated t Bu group occupies the apical position. Abstract : The coordination chemistry of the tridentate pincer ligand TL t Bu, which contains a bridging pyridine moiety and two electron‐rich imidazolin‐2‐imine moieties, is explored. The TL t Bu ligand strongly favours square‐planar geometries. The Fe II complex [(TL t Bu )Fe(OTf)][OTf] contains a cation with an unusual high‐spin ( S = 2) electronic ground state.